(untitled) (International Journal of Economics Management and Social Science, 2025)
This study aims to analyze the effectiveness of the e-filing system in improving individual taxpayer compliance in Indonesia. The e-filing system is part of the digital-based tax administration modernization that is expected to improve efficiency, transparency, and ease of SPT reporting services. The research method used a quantitative approach with a Likert-scale questionnaire instrument for 250 e-filing user respondents, supported by a qualitative approach through a review of previous research. The results show that e-filing effectiveness, digital literacy, and trust in the system have a significant positive influence on taxpayer compliance. System effectiveness is reflected in speed, ease of access, reporting accuracy, and data security. However, e-filing implementation still faces obstacles in aspects of digital literacy and technological infrastructure. These findings emphasize the importance of strengthening education, socialization, and digital infrastructure to increase the success of a modern tax system in Indonesia